Badania nad podręcznikami polonijnymi w kontekście zadań szkoły polskiej na obczyźnie = The studies over textbooks for Polish schools in The Unitet States, Great Brittain and Canada in the context of the mission of the Polish education abroad - Pelczar, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
The article presents the researching problems connected with textbooks, which were edited by the Polish education organizations in The United States of America, Great Brittain and Canada after the second world war. The author suggests to embrace the researching formal aspect of these publications - scheme of contents, criteria of choise titles, prefered kinds of literature and themes.
Keywords: Stany Zjednoczone Ameryki Północnej; Kanada; Wielka Brytania; polonia; szkolnictwo; podręczniki